Gaya Kepemimpinan dan Komunikasi Organisasi yang Selaras dengan Budaya di PT ASBO - Riandra Fahrezi, Revanza; Ilfandy Imran, Ayub (Jurnal The Messenger, 2025)
Purpose: This study aims to explore how leadership style contributes to build an effective internal communication as part of corporate communication that aligns with the company’s corporate identity. The research focuses on PT ASBO, a multinational company that have a unique and different corporate identity. This study aims to understand the dynamics between leadership, internal corporate communication, and their corporate identity in practice.   Methods: This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with a superior as key informant and subordinate as supporting informants within one department in PT ASBO where both of them works at the company for 17 years. Informants are selected to gain insights into leadership practices and communication patterns that happens in a specific department.   Findings: The findings indicate that manager’s participative leadership style engages team members in discussions and decision‐making, fostering internal corporate communication grounded in respect, empathy, audibility, clarity, and humble principles. This leadership style approach enhances and embodies the company’s corporate identity, particularly its values to diversity, equity, and inclusion.   Originality: This research offers a unique contribution by exploring how leadership style supports internal communication as a part of corporate communication aligned with the company’s corporate identity which is culture as one of the elements of corporate identity, particularly in a multinational company context that may contrast with local culture. Making it a valuable contribution to corporate communication.